PENGARUH PRASARANA FISIK, PROSES PELAYANAN DAN RESPONSIVENESS TERHADAP KEPUASAN NASABAH PADA LAYANAN ATM BNI CABANG MUSI PALEMBANG - Melvin Zumery; Tien Yustini; Neny Rostiati (Program Magister Manajemen Indo Global Mandiri University, 2021)
The purpose of this study was to determine the effect of physical infrastructure, service processes and responsiveness on customer satisfaction at BNI ATM services at the Musi Palembang branch partially or simultaneously. This research method uses descriptive and verification surveys, field data collection uses questionnaires, interviews and documentation techniques. This research is an associative research, where in this study there are variables that are related and can influence other variables. The population of this study was 100 customers at ATM services. Data processing uses SPSS 25 analysis tool. The results of the study show that physical infrastructure affects customer satisfaction, service processes affect customer satisfaction, responsiveness affects customer satisfaction, physical infrastructure, service processes and responsiveness affect customer satisfaction simultaneously.